HUBUNGAN ANTARA STRES DENGAN KECENDERUNGAN MEROKOK PADA WANITA - Erfin, Wilda (Universitas Ahmad Dahlan, 2014)
ABSTRACT This study aimed to determine the relationship between stress and smoking trends in women. The subjects were female smokers without specific age criteria from various groups, namely students, office workers, entrepreneurs, and housewives in Yogyakarta. Data collection instruments and scales using scale Stress Smoking trends and research data were analyzed using the technique of the Pearson product moment correlation with the help of SPSS 16 for windows. The analysis revealed a correlation coefficient between the two variables is rxy= 0,487 and (p<0.05). The effective contribution of the variable stress on smoking trends of 23.8%. The majority of the study subjects (51%) indicated having stress and smoking trends in the high category. The conclusion of this study is that there is significant positive relationship between stress and smoking trends. This suggests that the hypothesis is accepted, which means that the higher the intensity of the stress, the higher the frequency of smoking trends, conversely the lower the intensity of the stress, the lower the frequency of smoking trends.Keywords: stress, smoking trends.